Informally sourced solid fuel use: Examining its extent and characteristics of the users in the residential sector in Ireland. (January 2023) - Eakins, John; Sirr, Gordon; Power, Bernadette
Abstract: Developing effective policy solutions to transition away from the use of solid fuels for residential heating purposes can be hindered by the lack of reliable data on its use. One such issue is the extent of informal solid fuel use, that is, consumption from sources outside of formal commercial channels. This is an area which has been largely ignored in previous empirical research. Using a survey of residential solid fuel users, the extent of solid fuel use in the residential sector in Ireland from informal sources for two fuels, sod peat and wood, is quantified. Sod peat is found to be almost exclusively sourced informally while just over half of wood use is estimated to be sourced by households in this way. Factors including location, household income, being a primary user of the fuel and having strong cost motivations all effect the probability of sourcing solid fuels informally relative to formal sources. The sizeable extent to which informal sources of solid fuels are used in Ireland arising from the analysis in this paper, highlights the potential for substitution to this unregulated alternative. This should be carefully monitored for effective implementation of new and existing solid fuel regulations. Highlights: A survey of Irish households to examine informal solid fuel use is developed. Sod peat is almost exclusively sourced by households informally. Just over half of wood use is estimated to be sourced by households informally. Location, fuel dependence and cost motivations determine informal solid fuel choice. Monitoring informal use is important for the effectiveness of new solid fuel regulations.